The timeliness of quarterly financial reports of companies in Malaysia - Ku Ismail, Ku Nor Izah; Chandler, Roy (2003)
Timeliness has been recognized to be one of the characteristics that determines the relevance of accounting information. Because the timeliness of interim reporting has not been examined in any substantial way in Malaysia, this study examines the timeliness of quarterly financial reports published by companies listed on the Kuala Lumpur Stock Exchange (KLSE).In addition, this study extends prior research by determining the association between timeliness and each of the following company attributes - size, profitability, growth and capital structure.An analysis of 117 quarterly reports ended on 30 September 2001 reveals that all, except one company reported within an allowable reporting lag of two months.However, a large number of companies were making the most of the time given to announce their quarterly reports. The study also provides evidence that there is a significant association between timeliness and each of the four company attributes, and the association is in the hypothesised direction. Plausible explanations for these findings are provided. The findings may provide some implications for future regulations and research regarding the timeliness of financial reporting in Malaysia.